Concepção de homem omnilateral: uma proposta metodológica para além da abordagem crítico superadora na educação física - Dal Lin, Alessandra (2013)
This work aims to build a new methodological possibility in Physical Education from critical to surmounting critical approach with reference to the assumptions of historical materialism. It is known that the critical approach is surpassing reference in the historical context of Physical Education and presents theoretical and practical axis categories: totality, contradiction and historicity. Being a committed dialectical approach to the interests of the popular class is that a rigorous study and criticism of praxis presented by Group of Authors in the first 1992 edition was necessary. In order to do so, it is meant to seek for this materialism theory in Marx’s Economic and Philosophical Manuscripts of 1844 as well as in Marx’s and Engels’s The Dutch Ideology. Yet, although Marx hasn’t neither written on Education, nor proposed an educational pattern for society, his writings provided major support to a proper educational thought to scholars. It is from an understanding on Marx’s thinking, mainly from his thinking on the category of “labor”, that his study on this omnilateral man takes place. In fact, they are utter links to a broad understanding on Education. It is also pointed out in this investigation that Gramsci has taken Marx’s thinking, concerning human productive activity determinations and social relations concern in material life in the hegemonic organization and its implications on man himself concerning Education. Gramsci’s appropriation gave birth to a conception of this man omnilateral and this multilateral Education, for, like Marx, Gramsci apprehended Education in a broad and dialectical way. For this Italian scholar, Education gather man together with historicism and criticism. Productive and political forces meant to be in an emancipating context. This investigation intends to check this out. After proceeding to link the man omnilateral and multilateral Education with historical materialism, this thesis aims to bring together, as a propose, the critical approach of overriding criticism in Physical Education the formation of a new methodological approach to this critical area of knowledge. In doing so, it is important to give examples of Physical Education classes, if using the framework of historical materialism, in order to construct the conscious and also subject man in history by the discipline of Physical Education bias. The proposal presents a conception of Physical Education against hegemonic associated with life for the construction of a new conception of society and man-omnilateral.